(untitled) (Zien Journal of Social Sciences and Humanities, 2026)
This article analyzes the theoretical and practical aspects of developing interethnic communication culture among students in higher education institutions in the context of globalization. The processes of globalization have significantly intensified interactions among representatives of different cultures, thereby creating a strong need to develop intercultural communicative competence among students. The study highlights the importance of fostering tolerance, empathy, and cultural sensitivity as essential components of effective intercultural communication